Tunable piezoelectric metasurface for manipulating multi-mode guided waves in plate. (1st November 2022) - Shao, Shixuan; Xia, Rongyu; Li, Zheng
Abstract: To control the propagation of multi-mode guided waves in plate is very significant in nondestructive testing and structural health monitoring for identifying damage and detecting structural integrity. In this paper, a novel metasurface is proposed to simultaneously manipulate multi-mode guided waves in plate, including shear horizontal wave, symmetric mode and anti-symmetric mode Lamb waves. For controlling the guided wave propagation in plate, the functional unit is designed by a staggered arrangement of in-plane polarized and out-of-plane polarized piezoelectric patches attached on both surfaces of host plate to form a metasurface, and each piezoelectric patch is individually connected with negative capacitance circuit. The transmitted phase of each mode guided wave through the functional unit can be shifted arbitrarily in 0 ∼ 2 π range by adjusting the shunting negative capacitance circuits. Furthermore, the transmitted phase shifts profile along the metasurface can be coded to control the wave front of multi-mode guided waves in plate, and tunable functions including anomalous refraction and wave focusing can be realized. Results indicate that the proposed metasurface can simultaneously modulate and control the wave front of each mode guided wave to achieve wave mode splitting and purifying from multi-mode incident waves. In addition, a wave source shifter is realized by an annularly arranged metasurface to achieve equivalent wave source control. Therefore, the proposed piezoelectric metasurface has great potential in the fields of tunable manipulation of guided waves and design of smart devices. Highlights: First elastic metasurface to achieve tunable manipulation of multi-mode guided waves. The working frequency of the proposed metasurface can be tuned by the shunting circuit in a wide frequency range. Multiple functions including anomalous refraction and wave focusing are realized for each mode guided wave individually. Metasurface-based wave source shifter is further designed.